Development and Application of InDel Markers for Authentication of the Korean Herbs Zanthoxylum schinifolium and Zanthoxylum piperitum - Kim, Yonguk (Foods, 2019)
Zanthoxylum schinifolium and Zanthoxylum piperitum are the sources of the well-known traditional Korean herbal medicines “sancho” (prickly ash) and “chopi” (Korean pepper), respectively. Sancho and chopi are often indiscriminately mixed due to the similar appearance of the herbal materials when used as spices and herbal medicines. Moreover, commercial sancho and chopi products often contain adulterants, which is insufficient to ensure food efficacy and safety. In this study, we developed hypervariable insertion/deletion (InDel) markers to distinguish between sancho and chopi products by comparing the complete chloroplast genome sequences of four Zanthoxylum species deposited in the National Center for Biotechnology Information (NCBI) GenBank. Comparative analyses of the nucleotide diversity (Pi) of these Zanthoxylum genomes revealed four hypervariable divergent sites (trnH-psbA, psbZ-trnG, trnfM-rps14, and trnF-ndhK) with Pi > 0.025 among 520 windows. Of these four regions, including two genic and two intergenic regions, only psbZ-trnG yielded accurate PCR amplification results between commercial sancho and chopi products from the Korean herbal medicine market. We therefore selected psbZ-trnG, an InDel-variable locus with high discriminatory powers, as a candidate DNA barcode locus. This InDel marker could be used as a valuable, simple, and efficient tool for identifying these medicinal herbs, thereby increasing the safety of these spices and herbal materials in the food market.